Reopening Archives: Bringing New Contextualities into Archival Theory and Practice - Nesmith, Tom (Archivaria, 2006)
The opening of an archives is often an exciting occasion when access is gained to once inaccessible or previously unknown records. Archives today, though, are being reopened through growing interest in the history of records and archives. Approaches to this history have taken some radically new directions, influenced by postmodern insights. The profound implications for archival work of these new directions are still in conceptual infancy. This article offers an overview of this reopening of archives by outlining how archival ideas and work might be reconceptualized in light of these changing perspectives on the history of records and archives. RÉSUMÉ La relecture du passé est souvent une occasion excitante lorsqu’on donne ainsi accès à des documents qui étaient auparavant inaccessibles et inconnus. Le passé est aujourd’hui relu à cause d’un intérêt grandissant pour l’histoire des documents eux-mêmes. Influencées par les perspicacités post-modernes, les approches à cette forme d’histoire ont pris radicalement de nouvelles directions dont les implications profondes sur le travail archivistique sont encore aux premiers balbutiements. Cet article offre un survol de la relecture du passé en exposant comment les idées et le travail archivistique doivent être re-conceptualisés à la lumière des perspectives changeantes de l’histoire des archives.